The effect of tooth brushing frequency on plaque, gingival indices in Thamar Governorate (primary, intermediate, secondary schools) in Republic of Yemen (Mustansiria Dental Journal, 2004)
An oral health Survey was conducted ni Thamar Governorate schools (primary, intermediate, secondary schools). Certain aspects of oral health were investigated. The sample included 1758 students aged from 6-18 years old of both sexes (843 males, 915 females). The study has shown that 44.03% of the students did not brush their teeth, however, brushing Standards did not seem to be satisfactory, this was judged by the high plaque & gingival index mean for the sample and for different groups with ni the sample